Handbook of neuroendovascular surgery - Deshaies, Eric M.; Eddleman, Christopher S.; Boulos, Alan S. (Thieme, 2012)
"The evolution of vascular neurosurgery has continued and now provides a new set of tools to treat hemorrhagic and ischemic disease. Clearly, this evolution is becoming mainstream in neurosurgical training and adds to the body of knowledge that currently exists within traditional neurosurgical education. This text is an excellent reference for neurosurgical residents and fellows and, though not comprehensive, it is certainly ideal for quick reference and for triggering the evaluation of further information. The topics covered in this text span the field of neuroendovascular surgery and are an absolute must for medical students, residents, and fellows who are caring for these patients"--Provided by publisher